Culture of the Balto-Slavic Border Area: Good / Bad in the Language Consciousness of Latgale Youth - Isajeva, Elvira; Vasiljeva, Elina (Forum for Linguistic Studies, 2025)
Recent cognitive studies on language and linguistic units lead to the conclusion that language, as a person's cognitive ability, plays a central role in processing, storing and transmitting not only various types of objective knowledge about the world but also evaluative knowledge. The topicality of the theme considered in the given article lies in the study of the specifics of the functioning of both Russian as a diaspora language and Latvian in the same cultural space of the eastern region of Latvia-Latgale. The study aims to characterize the ways in which evaluative judgments are expressed in the linguistic consciousness of young Russian and Latvian speakers on the basis of modelling and analysis of the associative field of the stimulus words good and bad. Theory and practice of associative experiment were used as a methodological basis for the study. The words good/bad were suggested as stimulus words. The reactions obtained as a result of the experiment were analysed according to linguistic and cultural-contextual characteristics; as well as the modelled associative fields of the stimulus words were considered as a fragment of the image of the world of the Russians and the Latvians living in the south-eastern part of Latvia, its motives and assessments. Data processing and analysis allow defining the evaluative words good/bad in Russian and Latvian linguistic worldviews as full-fledged evaluative categories in the perception of young Russian and Latvian speakers in Latgale, since in their linguistic consciousness, not only dictionary meaning is actualised, but also multilevel contextual connotations.